2016
DOI: 10.4081/rt.2016.6282
|View full text |Cite
|
Sign up to set email alerts
|

Rare Aggressive Behavior of MDM2-Amplified Retroperitoneal Dedifferentiated Liposarcoma, with Brain, Lung and Subcutaneous Metastases

Abstract: Dedifferentiated liposarcoma (DDL) is a histologically pleomorphic sarcoma, traditionally defined as well-differentiated liposarcoma with abrupt transition to high grade, non-lipogenic sarcoma. It can occur as part of recurrent well-differentiated liposarcoma, or may arise de novo. DDL most frequently occurs within the retroperitoneum, and while it is prone to local recurrence, it usually has a lower rate of metastasis than other pleomorphic sarcomas. We describe a case of retroperitoneal dedifferentiated lipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…MDM2 is the most common amplified gene of differentiated liposarcoma, which is expressed at almost 100%. 9 Here, the presence of MDM2 amplification confirmed the diagnosis of dedifferentiated liposarcoma. 6 High amplification levels of MDM2 correlate with poor outcome in patients with dedifferentiated liposarcoma.…”
Section: Discussionmentioning
confidence: 61%
“…MDM2 is the most common amplified gene of differentiated liposarcoma, which is expressed at almost 100%. 9 Here, the presence of MDM2 amplification confirmed the diagnosis of dedifferentiated liposarcoma. 6 High amplification levels of MDM2 correlate with poor outcome in patients with dedifferentiated liposarcoma.…”
Section: Discussionmentioning
confidence: 61%
“…DDLPS accounts for about 18% of liposarcomas and was described by Evans in 1979. Most DDLPS are primary tumors (80–90%), and secondary dedifferentiation can occur in 10% of cases, mostly related to multiple recurrences of WDLPS [ 3 ]. DDLPS mostly affects middle-aged and elderly patients, and there is no significant gender difference.…”
Section: Discussionmentioning
confidence: 99%
“…Superficial liposarcomas are uncommon. A comprehensive review of the literature revealed 159 cases in the dermis and/or subcutis, with only 44 cases mentioning dermal involvement . Superficial liposarcomas have been reported in all four liposarcoma subtypes with PLPS being the most common (n = 95) .…”
Section: Discussionmentioning
confidence: 99%
“…DDL and myxoid are relatively uncommon (19 and 17 cases respectively) (Table shows the DDL cases). Only four of the 159 cases were metastases, including one case of DDL (Table ). All four metastatic cases originated from retroperitoneal primaries, consistent with the view that retroperitoneal tumors present additional surgical difficulties and may be delayed in their diagnosis due to their deep location, which can contribute to more aggressive behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation